2017
DOI: 10.1186/s12889-017-4161-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distribution of gastroenteritis viruses in Ouagadougou, Burkina Faso: seasonality of rotavirus

Abstract: BackgroundAcute gastroenteritis is one of the most common diseases among children and adults, and continues to cause a major problem of public health in Burkina Faso. The temporal pattern of rotavirus, norovirus, sapovirus, astrovirus, adenovirus and Aichivirus A was studied by examining prevalence of gastroenteritis viruses in association with meteorological variables in Ouagadougou, Burkina Faso.MethodsStool samples from 263 children under 5 years of age and 170 older children patients, adolescent and adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 35 publications
10
31
0
Order By: Relevance
“…RVA was detected throughout the year and followed a seasonal distribution, similar to previous reports in which peaks were observed in the winter months . Nafissatou et al .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…RVA was detected throughout the year and followed a seasonal distribution, similar to previous reports in which peaks were observed in the winter months . Nafissatou et al .…”
Section: Discussionsupporting
confidence: 88%
“…RVA was detected throughout the year and followed a seasonal distribution, similar to previous reports in which peaks were observed in the winter months [29][30][31] 5 years of age were correlated with temperature (r = À0.68, P = 0.01) [32], and our study also found a negative correlation between RVA-positive rate and temperature. As the total positive rate of acute gastroenteritis viruses had no correlation with temperature, it could not be the bacteria-induced food poisoning in summers that raised the total number of included diarrhoea outpatients which resulted in lower RVA-positive rates in winters.…”
Section: Rva-negative Samplesupporting
confidence: 91%
“…Similar observations regarding early RVA infections have been made in several other African countries and suggest a benefit of early schedule for RVA vaccination. Both RVA and NoV were detected predominantly during the winter season (December‐March), but with NoV peaking somewhat later (March; compared with January for RVA), similar to what has been described elsewhere …”
Section: Discussionsupporting
confidence: 86%
“…Several previous studies in Burkina Faso have shown RVA to be the predominant cause of severe childhood diarrhea, with detection rates ranging between 30% and 50% . In Burkina Faso, RVA gastroenteritis further has a marked seasonality with the vast majority of RVA diarrhea occurring in the dry cold period (December‐February), with NoV seasonality being less pronounced . Only few studies have investigated NoV in pediatric diarrhea in Burkina Faso (mild to severe), with detection rates of 12% to 21% …”
Section: Introductionmentioning
confidence: 99%
“…Acute diarrhea in childhood is the second most common cause of high morbidity and mortality and occurs mostly due to viral agents [1][2][3][4]. The most common viral agents are the association of rotavirus, adenovirus, and rotavirus-adenovirus [5][6].…”
Section: Introductionmentioning
confidence: 99%